2010
DOI: 10.1007/s10610-010-9133-8
|View full text |Cite
|
Sign up to set email alerts
|

It Looks Good, but What is it Like to Live There? Exploring the Impact of Innovative Housing Design on Crime

Abstract: This paper reports on the findings of a collaborative project (funded by the Home Office and managed by the Commission for Architecture and the Built Environment -CABE) which was conducted in late 2009 and early 2010. The project set out to strengthen and update the evidence base on the impact of design on a range of crime types -with a specific focus upon housing developments acclaimed for their innovative design and award winning architecture. This paper presents the findings of an in-depth assessment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 20 publications
1
59
0
1
Order By: Relevance
“…In the United Kingdom, Armitage [1] rated the physical characteristics of properties in West Yorkshire for core defensible space/ CPTED (referred to as 'Secured by Design' in the U.K.) variables including territoriality. Results showed that the absence of a real or symbolic barrier significantly increased the risk of burglary (see [3] for a more inclusive test of several additional CPTED variables; see also [9,10] for an exhaustive review of empirical tests of CPTED components). In the Netherlands, Reynald [25] found that territoriality played a significant positive role in explaining the variance in property crime on street-segments in The Hague, while the image/maintenance of the street segments emerged as significant but negative.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the United Kingdom, Armitage [1] rated the physical characteristics of properties in West Yorkshire for core defensible space/ CPTED (referred to as 'Secured by Design' in the U.K.) variables including territoriality. Results showed that the absence of a real or symbolic barrier significantly increased the risk of burglary (see [3] for a more inclusive test of several additional CPTED variables; see also [9,10] for an exhaustive review of empirical tests of CPTED components). In the Netherlands, Reynald [25] found that territoriality played a significant positive role in explaining the variance in property crime on street-segments in The Hague, while the image/maintenance of the street segments emerged as significant but negative.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some authors have included violent crime in the data analyzed, but with a few exceptions (see below) failed to disaggregate by crime type (e.g., Armitage et al 2011;Dhiman 2006;Fanek 1997;Greenberg and Rohe 1984;Jones and Fanek 1997;Long and Baran 2006;Nubani and Wineman 2005). In general, at least in the case of residential burglary, the evidence suggests that crime is more likely to occur on more accessible street segments.…”
Section: Introductionmentioning
confidence: 99%
“…Hillier and Sahbaz's results suggested that the higher the number of sides on which a dwelling is exposed (high rise flats above the ground floor not at all; detached houses on all four sides), the more vulnerable a property is to burglary. In a similar vein, properties located on a corner plot have been associated with higher risks of burglary (see Armitage et al 2011 In line with crime pattern theory, properties that are more likely to fall within offenders' 'awareness space' are at higher risk of crime. For example, houses that are located within proximity to a road junction, a main road, public footpaths, a commercial business establishment, a park, church or main road have all been shown to be at higher risk of burglary (Winchester and Jackson, 1982;Groff and La Vigne, 2001;Armitage, 2006).…”
Section: House Designmentioning
confidence: 77%
“…Housing estates that are situated on key routes, or provide short cuts from one place to another inhibit defensible space and diminish residents' abilities to exhibit territoriality. Several studies found that being located on a true cul-de-sac (with no pedestrian and vehicular connections) reduced the risk of victimisation (Armitage, 2006;Armitage et al, 2011;Johnson and Bowers, 2010). Other studies have shown that the closure of streets can lead to a reduction in crime levels (Zavoski et al, 1999).…”
Section: Neighbourood Layoutmentioning
confidence: 99%